Investigation of health promotion programs on food and nutrition in rural and First Nations communities of Northwestern Ontario [research project] - Collins, Stephanie (2009)
Purpose: To discover the status of health promotion programs based on food and nutrition in rural and First Nations communities in Northwestern Ontario, and the challenges, successes, and methodologies behind providing them. Background: Rural communities typically have lower health status than urban communities, and Aboriginals have lower health status than non-Aboriginals in Canada. Contributing factors for these disparities are discussed with a particular emphasis on the role of food and nutrition. Results: There are many programs involving food or nutrition in this area. Programs proved successful in using participatory models for intervention planning and delivery, having adequate training and ongoing support for interveners, delivering clear messages, using a rural lens, and using an Aboriginal focus. There were many challenges for health professionals, often surrounding food security, cost, and availability of food. Challenges did not always have solutions. More research is needed on the theoretical base of programs, and the challenges that face communities, their processes, and resulting health consequences in Northwestern Ontario specifically.